(untitled) (Journal of Medicine, 2017)
Background: Recently, we see in our clinical practice that many patients who are coming with generalized body aches and pains and diagnosed as fibromyalgia or chronic fatigue, not adequately responding to treatment. When their vitamin D level was done, it was found to be low and correction of their low vitamin D level improved their symptoms dramatically. Despite abundant sunshine in Bangladesh, allowing vitamin D synthesis all the year round, why our people are developing hypovitaminosis D inspired us to do this current study. Our present study is designed to estimate the prevalence of vitamin D deficiency among adult patients presented with aches & pains as well as to study the association of low vitamin D levels with different socio-demographic parameters. Methods: A cross sectional observational study was conducted among 212 adult patients aged 18 years and above presented with generalized body aches and pains, attended both outpatient and inpatient departments of Popular Medical College Hospital during the period of March’16- August’16 ( 6 months). Association between vitamin D status & the individual specific variables was statistically analyzed. Results: The prevalence of vitamin D deficiency among the study population was found to be100% in all age groups. Among 212 study population, 73.6% were female (n=156) & 26.4% were male (n=56). Mean Vitamin D level among male was 14.29 (SD 4.68) & among female was 12.64 (SD 4.74). The factors associated with severely deficient Vitamin D level were female sex, urban population, &obesity. It is alarming that 64.2% of our study population were totally unaware about the importance of sun exposure. Conclusions: Vitamin D status was associated with a number of socio-demographic variables. Knowledge of these variables may improve targeted education and public health initiatives. J MEDICINE Jan 2018; 19 (1) : 22-29